Digital Marketing Strategies for Agribusiness SMEs in Enhancing Competitiveness and Consumer Purchase Decisions: A Phenomenological Study in Nganjuk Regency - Moh. Rifqi Fauzi; Titin Yuni Astutik; Mohammad Alfa Rifhera Bintang; Meilina Tina Nurdiana (Journal of Economics and Social Sciences (JESS), 2026)
The purpose of this study is to examine how digital marketing helps agricultural MSMEs in Nganjuk Regency become more competitive and influence consumer purchasing decisions. Interviews, observations, and documentation were used in a qualitative method with a phenomenological design. The results show that digital marketing may boost consumer trust, broaden market reach, improve product visibility, and boost company competitiveness. However, there are still issues with its implementation, including a lack of human resources and insufficient computer literacy. As a result, digital marketing transformation—achieved through ongoing processes of adaptation, learning, and the development of digital competencies—emerges as a critical approach for the sustainability of agribusiness MSMEs.